1998
DOI: 10.1109/22.668678
|View full text |Cite
|
Sign up to set email alerts
|

Base-profile optimization for minimum noise figure in advanced UHV/CVD SiGe HBT's

Abstract: We investigate the base-profile design issues associated with optimizing ultrahigh vacuum/chemical vapor deposition (UHV/CVD) silicon-germanium (SiGe) heterojuction bipolar transistors (HBT's) for minimum broad-band noise. Using the simulator for cryogenic research and SiGe bipolar device optimization (SCORPIO), the impact of Ge profile, base doping level, and base thickness on minimum noise figure (NFmin) are quantitatively examined across the 055 C-125 C temperature range.We introduce a novel Ge profile for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0

Year Published

2000
2000
2004
2004

Publication Types

Select...
4
3
2

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 13 publications
0
23
0
Order By: Relevance
“…Errors in the SIMS profile cause large errors in some of the computed characteristics of the HBT. The IBM group [60,61] scale each SIMS doping profile (within 20%) so that the measured characteristic which depends most strongly on the profile shows best agreement with its computed value. The scaled profiles are designated as calibrated profiles.…”
Section: Doping Profilesmentioning
confidence: 99%
See 1 more Smart Citation
“…Errors in the SIMS profile cause large errors in some of the computed characteristics of the HBT. The IBM group [60,61] scale each SIMS doping profile (within 20%) so that the measured characteristic which depends most strongly on the profile shows best agreement with its computed value. The scaled profiles are designated as calibrated profiles.…”
Section: Doping Profilesmentioning
confidence: 99%
“…The calibrated profiles for a typical HBT [60,61] are shown in figure 12(a). With the calibrated profiles and reliable models for material parameters, the observed Gummel plots and cutoff frequencies agree with the simulated values within 10-20% [1,60,61]. Daimler-Benz AG (DBAG) SIMS profiles are shown in figure 12(b).…”
Section: Doping Profilesmentioning
confidence: 99%
“…For constant film stability, at a given geometry and doping, a higher and higher can only be realized in practice by pushing the edge of the Ge retrograde in the collector significantly closer to the EB junction (surface). The additional Ge can then be used to reduce the effective Gummel number in the neutral base for higher , and increase the Ge grading for higher [14], [15]. We are thus forced to trade highroll-off performance for improved .…”
Section: Sige Profile Designmentioning
confidence: 99%
“…Firstly, we report on works of Schumxher et al [I91 which have measured abrupt HBT 30 optimized with respect to the high frequency noise featuring minimum noise figure lower than I dB at I O GHz. Ansley et a1 [20] have also presented works on gradual HBT imcl they have shown that an appropriate base shape can leucl to vcry attractive performance since they report minimum noise figure as low as 0.5 dB at 2 GHz and they state that their technology are able to achieve HBT featuring minimuin noise figure in the 0.8 dB range at I O GHz. The works we present in this paper concerning the SiGe HBT are obtained on SiGe HBT optimized with respect to their L.F noise properties ancl doesn't constitute the state of the art.…”
Section: Iv-high Frequency Noise Behaviormentioning
confidence: 95%